2005
DOI: 10.1002/cncr.21264
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal soft tissue sarcoma

Abstract: The objective of the current study was to define the optimal treatment for patients with retroperitoneal soft tissue sarcomas (RPS). The authors conducted a review of the pertinent literature and found that the majority of patients had locally advanced RPS at the time of diagnosis. Surgery was the mainstay of treatment, and macroscopic total excision was feasible in approximately 50 -67% of patients. The 5-year probability of local control was approximately 50%, and the likelihood of developing distant metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
100
0
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(111 citation statements)
references
References 17 publications
1
100
0
10
Order By: Relevance
“…Approximately 50% of the STS patients will succumb to their disease because of metastasis or local relapse (2). The prognostic factors determining tumor progression and ultimately the patients' fate include tumor grade, size, location, depth, histological entity, positive resection margins and presence of local recurrence (3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 50% of the STS patients will succumb to their disease because of metastasis or local relapse (2). The prognostic factors determining tumor progression and ultimately the patients' fate include tumor grade, size, location, depth, histological entity, positive resection margins and presence of local recurrence (3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…8,[10][11][12][13] After undergoing macroscopically complete surgery alone, local recurrences develop in 20% to 75% of patients, and these can occur even after 5 years of follow-up. 1,8,10,[14][15][16][17][18][19] The estimated survival rate at 5 years varies between 12% and 75%, 6,13,20,21 and the cause of death for these patients usually is local recurrence, which is in sharp contrast to outcomes for patients with sarcoma of the extremities. 8,22 There is much controversy concerning the role of radiotherapy (RT) in the treatment of RSTS.…”
mentioning
confidence: 99%
“…1,8,10,[14][15][16][17][18][19] The estimated survival rate at 5 years varies between 12% and 75%, 6,13,20,21 and the cause of death for these patients usually is local recurrence, which is in sharp contrast to outcomes for patients with sarcoma of the extremities. 8,22 There is much controversy concerning the role of radiotherapy (RT) in the treatment of RSTS. Opponents argue that the lack of an overall survival (OS) benefit renders RT a treatment of little value.…”
mentioning
confidence: 99%
“…However, a study reported that even when combined resection of surrounding organs was performed, approximately 50% of soft tissue sarcoma cases showed local recurrence and 20% to 30% cases were found to have distant metastasis [9]. The mainstay of treatment is early diagnosis.…”
Section: Discussionmentioning
confidence: 99%